Red blood cell transfusions in preterm infants in 2021: a narrative review - Valete, Cristina Ortiz Sobrinho (2024)
Anemia is frequent in preterm infants. Red blood cell transfusion practices vary between different centers. The objective of this study was to review red blood cell transfusion practices in preterm infants between 2020 and 2021. This was a narrative review that included studies published on PubMed (Medline) and Web of Science between October 2020 and October 2021. Ten studies were included finally. Red blood cell transfusion frequency was variable. Some neonatal units did not report transfusion protocols. Most studies reported volumes of 10-15 ml/kg per transfusion. The implementation of an anemia care bundle and adoption of restrictive transfusion resulted in a reduction in the number of transfusions, the volume transfused, and a reduction in the rate of multiple transfusions. We suggest that neonatal units that care for preterm infants should have a transfusion protocol based on the best evidence available and this issue may improve.